STRUGGLE FOR MAKING DREAMS INTO REALITY IN SLUMDOG MILLIONAIRE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - NOR, IMAWAN (2010)
This research investigates how the struggle for life of the major character reflected in Danny Boyle‟s Slumdog Millionaire, especially viewed from an Individual Psychological Approach. Therefore, the study analyzes the movie in terms of its structural elements and based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources; they are primary and secondary data source. The primary data source and the object of the study is the movie Slumdog Millionaire itself, meanwhile the secondary data source are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. A result of the analysis shows the following conclusion: first, Steven Danny Boyle‟s wants to utter his idea that man has to struggle for his life to reach his goal of life. Through struggle, Jamal Malik as the major character learns to be more superior than before. In his struggle to reach a goal, he psychologically develops his personality to improve his creative power to solve the problems in the Slumdog Millionaire.